First report of Pneumocystis jirovecii pneumonia diagnosed with DNA sequencing in post-renal transplant patients in Sri Lanka - D. Gunarathne; A Amarasinghe; S. Wickramasinghe; R. Morel (Sri Lankan Journal of Infectious Diseases, 2021)
Pneumocystis pneumonia (PCP) caused by the fungus Pneumocystis jirovecii, is an opportunistic infection mainly in immunocompromised patients. Among renal transplant patients, PCP is a serious complication associated with a high mortality rate.   PCP was clinically diagnosed in a 53-year-old female and 35-year-old male post kidney transplant patients admitted to the National Hospital, Kandy, Sri Lanka.  Confirmation of the diagnosis by precise molecular and phylogenetic analysis is reported for the first time in Sri Lanka. The molecular data generated from the specimens obtained from these two patients can be further used for diagnostic and phylogenetic studies.